Obesity and spinal surgery: a systematic review - A.V. Evsyukov; O.G. Prudnikova; E.A. Matveev; M.S. Strebkova (Хирургия позвоночника, 2025)
Objective. A systematic review of the outcomes of surgical treatment of patients with spinal pathology in obesity. Material and Methods. A search was conducted in the Pubmed, EMBASE, ELibrary and Google databases for studies assessing the impact of obesity on the results and outcomes of spinal surgeries, the frequency and type of complications, and clinical and functional outcomes. The type of articles of interest was a systematic review and meta-analysis; the search period was 10 years. The literature search was performed by three researchers. The study was conducted in accordance with the international PRISMA guidelines for writing systematic reviews and meta-analyses. The levels of evidence reliability and recommendation strength gradations were assessed according to the ASCO guidelines. Results. A total of 1,695 articles were found in the databases using keywords, of which 1,618 were with full-texts, 1,161 — over the last 10 years, and 62 — systematic reviews and meta-analyses. The inclusion criteria were met by 17 articles. One article by domestic authors was additionally included in the sample by agreement of the authors of this publication. Thus, the study included 18 articles. Risk factors in obese patients undergoing spinal surgery include insulin resistance, arterial hypertension, atherogenic dyslipidemia, prooxidant and inflammatory activity, and muscle oxidative stress. Comparative analysis of surgical interventions in obese patients showed significantly higher duration of surgery, volume of blood loss, infectious and thromboembolic complications, and frequency of repeated interventions. According to all studies, the functional outcome of treatment in the long-term follow-up period does not differ in groups of obese and nonobese patients. Minimally invasive surgical interventions in obese patients showed advantages in terms of lower blood loss and shorter length of hospital stay without significant differences in functional outcomes. Technical difficulties in surgical interventions in obese patients are associated with surgical access, requiring additional traction of soft tissues and special instruments, which affects the duration of surgery, the volume of blood loss and, possibly, infectious complications. Conclusion. Obesity is a significant risk factor for perioperative complications in elective spinal surgery, the most important of which are blood loss, duration of surgery, surgical site infection, thromboembolism and repeated interventions. It is the operating surgeon who, based on all the initial data, determines the possibility of performing the intervention during the period of the patient’s visit, taking into account the risk factors, technical capabilities and features of surgical manipulations.